PD-L1-mediated gasdermin C expression switches apoptosis to pyroptosis in cancer cells and facilitates tumour necrosis - Hou, Junwei; Zhao, Rongce; Xia, Weiya; Chang, Chiung-Wen; You, Yun; Hsu, Jung-Mao; Nie, Lei; Chen, Yeh; Wang, Yu-Chuan; Liu, Chunxiao; Wang, Wei-Jan; Wu, Yun; et al. (Nature cell biology, 2020)
Although pyroptosis is critical for macrophages against pathogen infection, its role and mechanism in cancer cells remains unclear. PD-L1 has been detected in the nucleus, with unknown function. Here we show that PD-L1 switches TNFα-induced apoptosis to pyroptosis in cancer cells, resulting in tumour necrosis. Under hypoxia, p-Stat3 physically interacts with PD-L1 and facilitates its nuclear translocation, enhancing the transcription of the gasdermin C ( GSDMC ) gene. GSDMC is specifically cleaved by caspase-8 with TNFα treatment, generating a GSDMC N-terminal domain that forms pores on the cell membrane and induces pyroptosis. Nuclear PD-L1, caspase-8 and GSDMC are required for macrophage-derived TNFα-induced tumour necrosis in vivo. Moreover, high expression of GSDMC correlates with poor survival. Antibiotic chemotherapy drugs induce pyroptosis in breast cancer. These findings identify a non-immune checkpoint function of PD-L1 and provide an unexpected concept that GSDMC/caspase-8 mediates a non-canonical pyroptosis pathway in cancer cells, causing tumour necrosis. Hou et al. show that following hypoxia PD-L1 translocates into the nucleus to enhance transcription of GSDMC, which is then cleaved and activated by caspase-8 to cause pyroptosis in cancer cells.